Certain Indefinite Integrals Involving Gegenbauer Polynomials (Global Journal of Science Frontier Research, 2012)
In this paper we have established certain indefinite integrals involving Gegenbauer polynomials. The results represent here are assume to be new.
Keywords: Pochhammer Symbol; Gaussian Hypergeometric Function